New Approaches to the Direct Measurement of Capacitance. (1977) - Raven, M. S.; Raven, D.
Abstract : The limitations of conventional a.c. capacitance measuring techniques, for such measurements as MIS interface capacitance and measurements of large value electrolytics, has lead to a demand for new methods of capacitance measuring. This article reviews two new approaches which are presently being employed – the quadrature P.S.D. technique and time encoded ballistic techniques.